Factors Driving Purchase Intention of Reject Fashion Products at Factory Outlets: An Empirical Study in Makassar, Indonesia - Achmad Ridha; Lidya Anastasya (PT. Maju Malaqbi Makkarana, 2026)
This study investigates factors driving purchase intention toward reject fashion products at factory outlets in Makassar, Indonesia. Reject products garments that fail manufacturer quality control standards but are sold legally at discounted prices represent an underexplored segment of circular fashion consumption. Drawing on the Theory of Planned Behavior and the Value-Based Adoption Model, this study tests a structural model in which four antecedents defect transparency, price perception, environmental consciousness, and store reputation influence purchase intention through the mediating role of perceived value. A quantitative survey was conducted with 250 consumers who visited factory outlets in Makassar. Data were analyzed using PLS-SEM via SmartPLS 4.0. Common Method Bias was confirmed absent using Harman's Single Factor Test and Full Collinearity VIF. Results indicate that all four antecedents positively influence perceived value, which strongly predicts purchase intention. Price perception is the dominant driver, followed by store reputation, environmental consciousness, and defect transparency. Perceived value fully mediates the effect of defect transparency and partially mediates the remaining three antecedents. These findings contribute to circular fashion consumer behavior literature and offer practical guidance for factory outlet operators in Eastern Indonesia.